1999
DOI: 10.1007/s004180050413
|View full text |Cite
|
Sign up to set email alerts
|

CGRP immunohistochemistry in wound healing and dentin bridge formation following rat molar pulpotomy

Abstract: The aim of the present study was to investigate the neuropeptide CGRP in order to determine the effect on dentin bridge formation during the healing process after pulpotomy. First maxillary molars in 56-day-old Wistar rats (n=60) were used. The rats were killed for a neurohistopathological examination at 1, 3, 7, 14, and 28 days postoperatively. Neuronal changes in the residual pulp were studied using CGRP immunohistochemistry. By 1-3 days postoperatively, the CGRP-IR nerve fibers with abnormal beaded or knob-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 34 publications
1
20
0
1
Order By: Relevance
“…During pulpal repair an angiogenic response is essential for healing and reparative dentin formation (27). A role for CGRP in pulp healing and dentin bridge formation after rat molar pulpotomy has been previously suggested (28). Our results suggest that CGRP might have a role in the early stages of angiogenesis, as evidenced by the induction of HGF, PIGF, and bFGF by pulp fibroblasts after 24 hours of treatment.…”
Section: Discussionmentioning
confidence: 50%
“…During pulpal repair an angiogenic response is essential for healing and reparative dentin formation (27). A role for CGRP in pulp healing and dentin bridge formation after rat molar pulpotomy has been previously suggested (28). Our results suggest that CGRP might have a role in the early stages of angiogenesis, as evidenced by the induction of HGF, PIGF, and bFGF by pulp fibroblasts after 24 hours of treatment.…”
Section: Discussionmentioning
confidence: 50%
“…After recovery the rat molars were examined for dentin bridge formation. CGRP-immunoreactive nerve fibers were present in the pulp, and some terminated in the differentiating odontoblast layer and the initial matrix layer of the dentin bridge (10). The present results showed that CGRP is an effective agent in promoting pulpal healing by stimulating both osteodentin and tertiary dentin in the ferret canine.…”
Section: Discussionmentioning
confidence: 81%
“…Sensory denervation of rat molar teeth led to an accelerated loss of pulp tissue after occlusal exposure compared with innervated teeth with similar injury (8). CGRP-containing nerves have been observed near sites of tertiary dentin formation in rat molars (9,10). The role of neuropeptides, including CGRP, in mediating neurogenic inflammation, vascular changes in the pulp, and the healing of periapical lesions is extensively reviewed by Caviedes-Bucheli et al (11).…”
mentioning
confidence: 95%
“…Although the pulpal nerve fibers that contain CGRP have recently been shown to play an important role in the pulp response to inflammation and wound healing [10,14], no studies have yet elucidated the relationship between the CGRP-IR nerve terminals and the differentiation of undifferentiated mesenchymal cells into fibroblast-like cells and odontoblasts during the healing process after a pulpotomy with the use of immunoelectron microscopy. Our preceding paper described the relationship between CGRP-IR innervation and dentin bridge formation following a pulpotomy in the rat molar based on light microscopic immunohistochemistry [17]. In the present study, we attempt to further clarify whether the neuropeptide CGRP-IR nerve terminals are related to both the proliferation and cytodifferentiation processes and also the active function of renewing and regenerating odontoblasts in dentin bridge formation during the pulp healing using the calcium hydroxide method by immunoelectron microscopy.…”
Section: Introductionmentioning
confidence: 87%
“…According to the pulpotomy method [17], using a dental electric rotator with a sterilized water coolant, the left first maxillary molar was ground off with a diamond point bur and then the coronal pulp was removed with steel round burs (numbers 1/2 and 1) and cut with a spoon excavator at the coronal orifice of the root pulp. Thereafter, while alter- nately using 3% H2O2 and 5% sodium hypochlorite solution, the residual pulp was rinsed 3 times to clean the wound surface, and a sterile cotton pledget pellet was replaced at the wound surface for both hemostasis and drying.…”
Section: Methodsmentioning
confidence: 99%